Okay, again, let's try to solve here for the solution of the system.

Here, we can use elimination, or if you want to try; substituion.

We have x-y=3 and 7x-y=-3. If we add subtract both equations, the y's will cancel out, so that's good!

Therefore, we get x-7x=3-(-3), which is -6x=6 and x=-1.

Plugging the value of x for the value of y, we attain -1-y=3, -y=4, y=-4. So, it is a solution to the system! (B) works.

We can try plugging in this system to see if this works for both equations. Doing so, we get -1-(-4)=3, -1+4=3, True!, (C)

And, for the second equation, 7(-1)-(-4)=-3, -7+3=-3, Yes! So, (E) works!

Thus, the answer is (B), (C), and, (E).